Encountering Forests with Purpose: The Role of Routine and Ritual in (a) Nonreligious Practice - Banham, Rebecca (Journal for the academic study of religion, 2024)
As scholars grapple with terminology around nonreligion, ‘ontological security’ offers a useful way of articulating nonreligious ways of feeling safe, comfortable, and ethical in the world. This article explores the role of forests in the pursuit and maintenance of ontological security, drawing on the experiences of twenty-four Tasmanians. Participants engaged in acts of routine and ritual (meaningful, consistent practices) informing a sense of relationship between people and forests. As such, this article explores experiences with/in forests as a form of ‘nonreligious practice’: meaningful and significant experiences that tell humans about their place in the world, outside of a religious context. Many participants encountered forests in purposeful ways, engaging in rituals and routines which brought them ‘closer’ to nonhuman landscapes and species. To this end, this article asks to what extent we can understand ontological security, and routine/ritual, as nonreligious ways of navigating ethical, temporal, and ontological questions about one’s place in the world.